Management of acute stroke and urgent neurointerventional procedures during COVID-19 pandemic: recommendations on the Scientific Department on Cerebrovascular Diseases of the Brazilian Academy of Neurology, Brazilian Society of Cerebrovascular Diseases and Brazilian Society of Neuroradiology - MONT’ALVERNE, Francisco José Arruda; LIMA, Fabrício Oliveira; NOGUEIRA, Raul Gomes; FREITAS, Carlos Clayton Macedo de; NETO, Octávio Marques Pontes; SILVA, Gisele Sampaio; OLIVEIRA, Maura Salaroli de; FRUDIT, Michel; CALDAS, Jose Guilherme Mendes Pereira; ABUD, Daniel Giansante; CONFORTO, Adriana Bastos; CARVALHO, Fernanda Martins Maia; DIAS, Francisco Antunes; BAZAN, Rodrigo; AVELAR, Wagner Mauad; MORO, Carla Heloísa Cabral; MAGALHÃES, Pedro Silva Correa de; MIRANDA, Maramelia; BARBOSA, Leandro de Assis; FIOROT, José Antonio, JUNIOR; CARDOSO, Fabrício Buchdid; REBELLO, Leticia Costa; PARENTE, Bruno de Sousa Mendes; FARIA, Mário de Barros; FREITAS, Gabriel Rodriguez de; ZÉTOLA, Viviane de Hiroki Flumignan; OLIVEIRA-FILHO, Jamary; BEZERRA, Daniel da Cruz; RODRIGUES, Jorge Luis Nobre; KUSTER, Gustavo; MARTINS, Sheila; CARVALHO, João José Freitas de (Arquivos de Neuro-Psiquiatria, 2020)
Introduction: Although the 2019 severe acute respiratory syndrome coronavirus 2 infection (SARS-CoV-2, COVID-19) pandemic poses new challenges to the healthcare system to provide support for thousands of patients, there is special concern about common medical emergencies, such as stroke, that will continue to occur and will require adequate treatment. The allocation of both material and human resources to fight the pandemic cannot overshadow the care for acute stroke, a time-sensitive emergency that with an inefficient treatment will further increase mortality and long-term disability. Objective: This paper summarizes the recommendations from the Scientific Department on Cerebrovascular Diseases of the Brazilian Academy of Neurology, the Brazilian Society of Cerebrovascular Diseases and the Brazilian Society of Neuroradiology for management of acute stroke and urgent neuro-interventional procedures during the COVID-19 pandemic, including proper use of screening tools, personal protective equipment (for patients and health professionals), and patient allocation.
Keywords: neurointerventional treatment; coronavirus infections; stroke